2018
DOI: 10.3126/bibechana.v16i0.19190
|View full text |Cite
|
Sign up to set email alerts
|

Morphological study on particulate matter of Kathmandu valley

Abstract: Air borne particulate matter (PM) depending on size, shape, concentration, and chemical composition can cause multitude of health issues. In this study, we report the morphological study of dust samples obtained from twenty different locations of Kathmandu valley by imaging the sample directly by a bright field optical microscope. We find that the average size of particles in all the samples examined below 10 micrometer. Individual examination of particles revealed that significant number of particles asymmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
4
2
0
Order By: Relevance
“…As shown in Fig. 3B, a total of 98% particles were smaller than 10 μm, which is in consistent with a recent study reported by our group (Rauniyaar, Aryal & Neupane, 2019). Thus, the filtering efficiency of the face mask reported in Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As shown in Fig. 3B, a total of 98% particles were smaller than 10 μm, which is in consistent with a recent study reported by our group (Rauniyaar, Aryal & Neupane, 2019). Thus, the filtering efficiency of the face mask reported in Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Bright filed microscopy is frequently used in the determination of number density of micro-meter sized objects (Ricardo & Phelan, 2008; Drey, Graber & Bieschke, 2013; Rauniyaar, Aryal & Neupane, 2019). The accuracy in such measurement is high if: (1) light scattering efficiency of an object to be imaged is high so they can be contrasted from the background, and (2) individual dispersion in the field of view can be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Fig. 3B, 98% particles were smaller than 10μm which is in consistent with a recent study reported by our group (Rauniyaar, Aryal & Neupane, 2019). Thus, the filtering efficiency of face mask reported in Fig.…”
Section: Filtering Efficiencysupporting
confidence: 92%
“…3B. Around 98% particles in ambient air was smaller than 10μm which is consistent with a recent study reported by our group (Rauniyaar, Aryal & Neupane, 2019).…”
Section: Filtering Efficiencysupporting
confidence: 92%
“…Several studies have suggested that mineral distribution and composition of airborne particulate matter is important to understand the health impact of a region [13,29,30,31,32,33,34,35]. Recently, we reported an optical microscopic study on the air dust samples collected from different core areas of Kathmandu Valley in April 2018 [36]. It was found that significant number particles in the samples to be asymmetric.…”
Section: Introductionmentioning
confidence: 96%